Processing of diphasic mullite and mullite-alumina composite precursors - Minghua Zhou (2021)
Diphasic mullite and mullite-alumina composite precursors were prepared from the silica source (Na2SiO35H20) (a cheap industrial by-product) and the alumina source (AlCl36H2O) by a coprecipitation method (aluminium nitrate and colloidal silica were used to prepared mullite-alumina composite precursor as a comparison), aiming to understand the mullite and mullite ceramic from the initial stage of preparation and eventually develop the industrial application potential. The investigations were mainly carried out in the following aspects: (i) the influences of the coprecipitation pH on the mixing degree of alumina-containing species and silicon-containing species and the electrophoretic behaviours, (ii) the aging effects on the physico-chemical characteristics of the coprecipitated precursors, (iii) the interaction between silica matrix and alumina crystallites mullite and mullite-alumina composite precursors and its influence on the formation of α-alumina in mullite-alumina composite (iv) the microstructures and microstructural evolution of mullite and mullite-alumina composite were studied by means of different shaping methods, (v) the densification of coprecipitated diphasic mullite-alumina composite precursors was investigated as comparing with the diphasic mullite-alumina composite obtained by a colloidal method (from colloidal silica and aluminium nitrate) (vi) evaluation of some sintered mullite and mullite-alumina composite compacts. The diphasic character of the precursor becomes stronger as pH increases and results mainly from the large differences in hydrolysis and precipitation rates between aluminium- and silicon-containing species. Alumina containing species and silica containing species in the coprecipitated mullite and mullite-alumina composite precursors were mixed in nanometer scale and react independently up to the point of mullitization. Hydrothermal aging experiments change the electrophoretic behaviour, morphology, hydration degree and chemical environments of silicon ions and aluminium ions of the particles in the mullite suspension obtained by a coprecipitation method. With the increase in the aging time, the isoelectric point (IEP) of the particles' surface gradually decreased. The hydration degree of the precursor was reduced. These phenomena were enhanced by autoclave aging at 230 °C which transformed all bayerite into boehmite. These transformations were accompanied by some replacement of ≡Si-O-Si≡ bonds by ≡Si-O-Al= bonds and smoothing of the particle surface, the precursor becomes more homogeneous after autoclave aging. Besides the mixing degrees of the alumina-containing species and silica-containing species have strong influence on the morphology of the pure mullite matrix grains, processing could also change the microstructure in pure mullite matrix. Uniform microstructure of pure mullite matrix without abnormal grain growth could also be obtained from diphasic precursor by fractionating the mullite precursor (milling, sedimentation etc.), manipulating and controlling interparticle forces as practiced in colloidal science to obtain green bodies with less heterogeneities by slip casting. At low sintering temperature (1400 °C), the excess alumina in mullite-alumina composite derived from a coprecipitated diphasic precursor exists as low crystallized and fine alumina crystallites distributed among the small mullite grains. The nucleation and grain growth of α-Al2O3 takes place at about 1500 °C. With the coalescence of the small mullite grains in a preferred orientation, the excess alumina precipitates out in the form of α-Al2O3 platelets. The aspect ratio of the alumina platelets decreases with the increase in the soaking time at 1600 °C which seems to be due to an anisotropic diffusion of aluminium ions. The densification of the two diphasic composite precursors requires a high temperature up to 1600 °C either by pressureless sintering or pressure assisted sintering due to the existence of the excess alumina after the mullitization (around 1200 °C) which retards the further densification. The mechanical properties of the mullite-alumina composites (micro hardness and fracture toughness) are better than the pure mullite matrix due to the reinforcement of the alumina second phase.